Teaching Balaghah for the Purpose of Appreciation of Al-Quran Language - Aflisia, Noza; Hendrianto; Kasmantoni (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2021)
Abstract This paper displays some modern linguistic approaches in teaching balaghah. Not only outlines the basic assumptions that underlie the use of these approaches in the study of balaghah, but also direct examples taken from the verses of the Qur’an. This study is considered very important to learn because will be discussed in this paper it can help Balaghah teachers in providing Balaghah materials with appropriate approaches. The approaches will help learners, so that learners gain a proper understanding of Balaghah theory and its application. This paper is the result of a literature review sourced from various national and international scientific books and articles. Data analysis is done by sorting the information and data found, classifying the data, finding relationships and examples directly from the Qur'an, verifying and concluding and analyzing. The results revealed several approaches in the teaching of Balaghah, namely the syntactic approach (Balaghah as a continuation of Nahwu), semantics (Dilalah as the main component in Balaghah), stylistics (Balaghah as Arabic stylistics), pragmatics (pay attention to communication between speaker and speaker), and semiotics. (digging the meaning of a sign through aspects of communication). Keywords: Balaghah, Teaching, Al-Quran, Language, Arabic